An innovative approach to recovery of fluctuating industrial exhaust heat sources using cascade Rankine cycle and two-stage accumulators. (1st August 2021) - Li, Pengcheng; Cao, Qing; Li, Jing; Lin, Haiwei; Wang, Yandong; Gao, Guangtao; Pei, Gang; Jie, Desuan; Liu, Xunfen
Abstract: The fluctuating property of the heat source is a technical obstacle of waste heat recovery, which leads to part-load operation and reduced economics. This work presents a novel system to mitigate the fluctuations by using steam-organic Rankine cycles (RC-ORC) and two-stage steam accumulators. The system can switch between isothermal heat storage and discharge simply by the regulation of water mass flow ( m 2 ) from the low-temperature accumulator (LTA) to the high-temperature accumulator (HTA). In the heat charge mode, m 2 rises when the inlet temperature or mass flow of the heat source increases. The water level of the HTA elevates. Analogously, in the heat discharge mode, m 2 decreases and more water accumulates in the LTA. The RC-ORC operates under the rated condition consistently through the unique structural design. The fundamentals and features of the system are illustrated. Given two typical heat source conditions, the fluctuations in thermal efficiencies are minor (15.63–15.84% and 19.57–19.70%). Thermo-economic estimation of the tanks indicates that the steel cost is roughly 1306 $ and 432 $, respectively. Compared with the single-stage ORC using stream control, the normalized investment cost ( N I C ) is reduced by 888–925 $/kW. Highlights: A novel attempt to tackle waste heat recovery challenge of fluctuating sources. Stable power generation is guaranteed with a maximum heat recovery rate. Unique operation of organic Rankine cycle driven parallelly by two evaporators. Two cases of fluctuating flow rate and temperature are investigated. A reduction of the normalized investment cost of 888–925 $/kW is achieved.